2018
DOI: 10.1021/acs.analchem.8b03668
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Experimental Conditions on the Ratio of 25-Hydroxyvitamin D3 Conformers for Validating a Liquid Chromatography/Ion Mobility-Mass Spectrometry Method for Routine Quantitation

Abstract: The utility of adding ion mobility (IM) to liquid chromatography/mass spectrometry (LC/MS) for quantitation of 25hydroxyvitamin D 3 (25OHD3) is evaluated. Sodiated 25OHD3 ions adopt both closed and open conformations, whereas the stereoisomer 3-epi-25-hydroxyvitamin D (epi25OHD), when sodiated, adopts only a closed gas-phase conformation. The unique open conformation for sodiated 25OHD3 permits unambiguous quantitation. Nonetheless, the ratio of open versus closed gas-phase conformations for sodiated 25OHD3 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 45 publications
0
22
0
3
Order By: Relevance
“…In this work, one of two possible conformers of the same ion is quantified under the assumption that the unique conformer is representative of the solution concentration. Work in our lab has shown that the ratio of the conformers depends on the instrument settings and ion flux within the mass spectrometer where the unique open conformer converts to the closed conformer, but potential bias from interconversion can be avoided with the use of an isotopically labeled internal standard, as shown in our previous work 25 .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In this work, one of two possible conformers of the same ion is quantified under the assumption that the unique conformer is representative of the solution concentration. Work in our lab has shown that the ratio of the conformers depends on the instrument settings and ion flux within the mass spectrometer where the unique open conformer converts to the closed conformer, but potential bias from interconversion can be avoided with the use of an isotopically labeled internal standard, as shown in our previous work 25 .…”
Section: Introductionmentioning
confidence: 75%
“…As seen in Figure 3, under ideal conditions, approximately 10% of 25OHD3 remains in the closed conformer. Additionally, it has been shown that the open conformer readily converts to the closed conformer under high-energy conditions 25 . Strategies that reduce the abundance of the closed conformer of 25OHD such as alternative cation adducts 40 , could be implemented to improve simultaneous quantitation of the epimers, but introduction of alternative cations into the LC/IM-HRMS method is not straightforward and the utility of rapid quantitation of the epimers is low.…”
Section: Methods Validation Figures Of Meritmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobilitas ion (221)(222)(223)(224)(225) dapat dihitung dengan pengukuran sebenarnya jarak yang ditempuh setiap ion dalam waktu tertentu dengan metode batas bergerak.…”
Section: Mobilitas Ion (U)unclassified
“…Mobilitas ion (221)(222)(223)(224)(225) merupakan kecepatan ion pada beda potensial antara kedua elektroda atau bias dibilang perbandingan antara laju dan kuat medan. Mobilitas Ionik dalam air pada suhu 298 K. (243)(244)(245)(246)(247)(248)(249)(250)(251)(252)…”
Section: Mobilitas Ionunclassified